2018
DOI: 10.3389/fgene.2018.00646
|View full text |Cite|
|
Sign up to set email alerts
|

DNA Methylation and Gene Expression of Matrix Metalloproteinase 9 Gene in Deficit and Non-deficit Schizophrenia

Abstract: The biological pathology of deficit schizophrenia (DS) remains unclear. Matrix metalloproteinase 9 (MMP9) might be associated with neural plasticity and glutamate regulation, involved in schizophrenia pathogenesis. This study explores gene expression and DNA methylation of MMP9 in peripheral blood mononuclear cells (PBMCs) and their relationship with clinical symptoms in DS and non-deficit schizophrenia (NDS). Pyrosequencing was used to determine DNA methylation at CpG sites in exon 4 and exon 5 of MMP9 in 51 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(11 citation statements)
references
References 68 publications
2
9
0
Order By: Relevance
“…Previous research suggested that negative symptoms may indicate neuronal damage [40] and that predominantly negative symptoms are associated with neurodevelopmental abnormalities [41]. Additionally, our finding is in line with recently published studies reporting that MMP9 mRNA expression is more pronounced in deficit schizophrenia [38,42]. Last, it has previously been demonstrated that MMP9 influences hippocampal and prefrontal N-methyl-D-aspartate receptor (NMDA) activity [38,42].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Previous research suggested that negative symptoms may indicate neuronal damage [40] and that predominantly negative symptoms are associated with neurodevelopmental abnormalities [41]. Additionally, our finding is in line with recently published studies reporting that MMP9 mRNA expression is more pronounced in deficit schizophrenia [38,42]. Last, it has previously been demonstrated that MMP9 influences hippocampal and prefrontal N-methyl-D-aspartate receptor (NMDA) activity [38,42].…”
Section: Discussionsupporting
confidence: 92%
“…Our finding of elevated MMP9 plasma levels is in line with previous studies demonstrating higher peripheral activity of MMP9 [37] and its increased blood concentration [24,25] in patients with schizophrenia. It has been proposed that abnormal MMP9 levels might be a useful peripheral biomarker of schizophrenia [24], potentially discriminating patients from healthy individuals [38]. Indeed, given MMP9 distribution and upregulation of this protein might explain several processes that are disturbed throughout the lifespan in schizophrenia.…”
Section: Discussionmentioning
confidence: 99%
“…Gao et al . 39 reported a specific abnormality in peripheral expression of the matrix metalloproteinase 9 gene, MMP9 , and its methylation, indicating a potentially different pathological mechanism underlying a specific subgroup of schizophrenia, which includes deficit schizophrenia patients. In turn, gene expression profiling of the dorsolateral and medial orbitofrontal cortex in schizophrenia patients 40 identified seven novel genes, including KAT7 and EVI2A , and previously reported gene TARDBP (all residing within cluster 1) that are differentially expressed in several brain regions, including prefrontal cortical regions, in patients with SCZ.…”
Section: Discussionmentioning
confidence: 99%
“…Archives Medical Review Journal Another recent study on the gene SLC6A4 encoding the serotonin transporter (5-HTT) found significant hypermethylation at one CpG site in male patients with SZ 65 . A recent study by Gao et al showed that MMP9, which plays a role in the regulation of the extracellular matrix, is hypomethylated in SZ patients with deficiency compared to non-deficient SZ patients 66 . In a recent study conducted in 2020, CpG regions in FAM63B were found to be significantly hypomethylated in blood samples from SZ patients 67 .…”
Section: Epigenetics In Schizophrenia: Focus On Dna Methylationmentioning
confidence: 99%